Vikings and iPads: how iPads may influence historical thinking in the classroom - Helge Pederson; Lisbeth Bergum Johanson (University of Aberdeen, School of Education, 2021)
The last few years have seen the introduction of technology in Norwegian classrooms without much research data on how this affects learning. This article discusses whether the introduction of iPads in a Norwegian classroom influences how history is taught and what the pupils learn. One could imagine that when iPads with its learning applications and unlimited access to the internet replaces textbooks and pen and paper as the main learning platform it might help the transition from mainly gaining "knowing what" knowledge to also gaining "knowing how" knowledge, consequently learning historical thinking. We explore whether this is the case. We did this by observing two sixth grade classes at two different schools both learning about the Viking age over a six week period. One class using iPads as their main learning platform and one using a broader set of learning platforms. The aim of this article is to contribute to the ongoing academic and popular discourse on how the widespread use of digital tools such as iPads impacts on learning, and in this case, if it influences the learning of history.